2018
DOI: 10.1186/s12885-018-4744-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical liver resection on circulating tumor cells in patients with hepatocellular carcinoma

Abstract: BackgroundThis study explored the effect of liver resection on perioperative circulating tumor cells (CTCs) and found that the prognostic significance of surgery was associated with changes in CTC counts in patients with hepatocellular carcinoma (HCC).MethodsOne hundred thirty-nine patients with HCC were consecutively enrolled. The time-points for collecting blood were one day before operation and three days after operation. CTCs in the peripheral blood were detected by the CellSearch™ System.ResultsBoth CTC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 30 publications
4
75
0
1
Order By: Relevance
“…The prognosis of Stage I/II is not only associated with tumor size and number, vascular invasion and/or lymph node metastasis but also might be influenced by circulating tumor cells. Perioperative circulating tumor cells have been associated with survival in HCC 28‐30 …”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of Stage I/II is not only associated with tumor size and number, vascular invasion and/or lymph node metastasis but also might be influenced by circulating tumor cells. Perioperative circulating tumor cells have been associated with survival in HCC 28‐30 …”
Section: Discussionmentioning
confidence: 99%
“…The presence and quantity of CTC are associated with a worse clinical outcome; for example, in CRC, high CTC counts are associated with a poor prognosis and significantly decreased survival . In the majority of patients with cancer, for example, CRC, CTC can be detected already preoperatively, but surgery contributes to a increase in their number . For instance, the CTC count was found to be higher postoperatively compared to preoperative counts in a prospective study on patients undergoing resection for lung cancer, hepatocellular carcinoma and gastric cancer …”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…For example, Yu et al showed that there were a mean of only 1.15 CTCs per 7.5 ml of blood in patients with operable hepatocellular carcinoma (HCC). 2 Patients with 2 or more CTCs per 7.5 ml of blood had inferior disease-free survival and overall survival than those with less than 2 CTCs per 7.5 ml blood. 2 Precise measurement of the number of CTCs at this level is impossible, even when only considering sampling errors.…”
Section: Introductionmentioning
confidence: 88%